INVESTIGATION OF BASALT REINFORCEMENT CROSSBARS - Umarov Shodiljon Abdug‘ofurovich (Journals Park Publishing, 2023)
In recent years, the President of the Republic of Uzbekistan and the Cabinet of Ministers have been making important decisions to raise the standard of living of the population and improve living conditions. In the implementation of these decisions, it is necessary to create economically inexpensive construction structures with high durability, uniqueness, and their practical application in the construction of production enterprises, residential buildings, and engineering structures, which are necessary for the economy.
Keywords: composite, basalt, concrete, flexibility, strength, messura, polymer.